The Position of Traditional Law as a Source of Law in the Civil Law System in Indonesia - Dedi Iskandar; Nelvitia Purba; Ismed Batubara; Yeltriana Yeltriana (Jurnal Akta, 2022)
Indonesian law essentially comes from four sources of law, namely customary law, Islamic law, ex-colonial law and ratified international treaties. But what makes it sad is that from these four sources of law, customary law is left behind or forgotten, it looks inferior compared to other laws. In scientific forums it is only used as research material and academic studies and is narrated rhetorically. Against this background, the problem studied in this research is how the position of customary law in the national legal system with a civil law pattern in Indonesia is. The research method used is normative juridical sourced from primary, secondary and tertiary legal materials. The results show that traces of customary law are scattered in legislation, as legal principles in positive law in Indonesia and also in jurisprudence. Research findings that customary law fulfills two requirements of reality and ideals as the primary source of law in Indonesian legislation.